Pollution haven hypothesis (PHH) - Ozcan, Burcu (Edward Elgar Publishing Ltd., 2025)
This entry explains the pollution haven hypothesis (PHH) theoretically. The PHH is a popular empirical research subject for energy and environmental economics researchers. It deals with the relationship between foreign direct investment (FDI) and energy consumption/environmental quality. The hypothesis suggests that developing or undeveloped countries that host FDI will become pollution havens due to foreign capital inflows. Since developed countries have strict environmental regulations, multinational companies in developed countries cannot carry out energy- and pollution-intensive production processes in their own countries. However, developing and undeveloped countries need more FDI inflows to grow and fight poverty and unemployment problems. Therefore, they must host developed countries’ energy-intensive and dirty production processes. In short, the hypothesis states that FDI inflows lead to environmental pollution by increasing energy consumption in developing and undeveloped countries. In addition, at the end of this entry, the theoretical explanations against the PHH and a few empirical studies that support and do not support the hypothesis have been included. © The Editor and Contributing Authors Severally 2025
Keywords: Developed Countries; Developing Countries; Energy Consumption; Environmental Pollution; Foreign Direct Investment (FDI); Pollution Haven Hypothesis (PHH)